STRATEGI TRANSFORMASI DIGITAL VIETNAM DALAM PEMULIHAN SEKTOR PARIWISATA INTERNASIONAL HO CHI MINH PASCA COVID-19 - Winanda, Riesa; Rasyidah, Resa (STAH Dharma Sentana Sulawesi Tengah, 2025)
Vietnam's closure of international flight access has caused Ho Chi Minh's tourism numbers to plummet. In 2020, when COVID-19 broke out, Ho Chi Minh's international visitors dropped from 8.6 million to 1.3 million before Vietnam finally closed international flight access, which made Ho Chi Minh's international visitation rate zero in 2021. Therefore, to recover the tourism sector, the Vietnamese government is transforming its tourism strategy to become more digital to adapt to the pandemic. This paper discusses the Vietnamese government's digital transformation strategy for restoring Ho Chi Minh's international tourism sector after the Covid-19 pandemic. The research method used is a descriptive qualitative with a secondary data collection method through a literature review of credible sources such as books, articles, journals, and official websites. Through the research conducted, it was found that the Vietnamese government made digital transformation efforts to restore its tourism industry after the Covid-19 pandemic. The Vietnamese government realizes the importance of digital transformation in the tourism industry to adapt to the Covid-19 global pandemic. The Vietnamese government recognizes the importance of digital transformation in the tourism industry in adapting to the global Covid-19 pandemic. The Vietnamese government has aggressively pursued digital transformation for tourism in Ho Chi Minh City since 2020 and will continue until 2024.